Digital transformation of society – problems and prospects of sociological study - Korshunov, Gennady P. (Journal of the Belarusian State University. Sociology, 2019)
The article presents a variant of problem and perspective research of processes related to the development of scientific and technical progress and the introduction of information and communication technologies in all spheres of life: in economics and politics, in social and cultural spheres.
Keywords: digitalization; information and communication technologies; economics; culture; politics; social sphere